Modelling of stock dynamics for spiny king crab Paralithodes brevipes at southern Kuril Islands using a finite-difference model with delay - Igor S. Chernienko (Известия ТИНРО)
The information on fishery object limited by CPUE data and fragmentary data on age and size is sufficient for production models. However, this type of models is improper for long-living species, as crabs, because of problem with assumption on equilibrium stock. Describing dynamics of a single year-class, these models average the parameters for all generations that impedes to use them for assessment of crabs stocks. Finite-difference models with delay are more promising in this case. Deriso-Snute finite-difference model with delay was used for simulating of the spiny king crab biomass dynamics at southern Kuril Islands and forecasting of TAC for this species. Parameters of the model were estimated using the algorithm of sampling by scheme of Markov chain. The model is relatively simple and undemanding to data - time-series of commercial catch per effort is sufficient for its simplest version. Results of modeling are comparable with the results of cohort models.